Height−diameter relationships in Brutian pine stands in Kurşunlu Waterfall Nature Park - ŞEN, Dilek; SAĞLAM, Fadime (Prensip Publishing, 2024)
In the scope of this study, the aim was to develop height−diameter models for Brutian pine forests located within the boundaries of Kurşunlu Waterfall Nature Park in Aksu district of Antalya province. For this purpose, height−diameter data for 516 sample trees were randomly divided into model (422 trees) and control (94 trees) groups. Using height−diameter values obtained from 422 sample trees, parameter estimates were made for three models that are commonly used in the literature and successfully reflect height−diameter relationships. The best model was evaluated based on four success criteria: Coefficient of Determination (R2), Root Mean Square Error (RMSE), Mean Absolute Error (MSE), and Akaike Information Criterion (AIC). The results of the evaluation indicated that the M2 (Meyer) model, which exhibited the lowest ranking value, was the most effective model. The observed and predicted height values of the trees in the independent data group were compared using the Student’s t−test. The results of the test indicated that the observed and predicted height values were statistically indistinguishable (p>0.05). The height−diameter model developed as a result of the study will serve as a significant tool for biomass and carbon stock estimation.